Hydrology and hydroclimatology : principles and applications - Karamouz, Mohammad (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2013)
"This book presents a systematic approach to understanding and applying the principles of hydrology and hydroclimatology, examining the interactions among different components of the water cycle. It takes a fresh look at the fundamentals and challenges in hydrologic and hydroclimatic systems as well as climate change. The author describes the application of nontraditional data sets and new investigation techniques to water-related problems. He also examines long lead forecasting and simulation, time series analysis, and risk and uncertainty in hydrologic design"--
Includes bibliographical references and index.
Keywords: Climatology; Hydrologic cycle; Hydrometeorology; SCIENCE / Environmental Science; TECHNOLOGY & ENGINEERING / Environmental / Water Supply